Adenosine Diphosphate Breakdown by the Plasma of Different Species and by Human Whole Blood and White Cells - Bolton, C. H; Emmons, P. R (Thrombosis and Haemostasis, 1967)
1. The breakdown rate of ADP (200 µM/ml) by the platelet-poor plasma of the animals studied (human, rabbit, cat, sheep and rat) is consistent within a species and characteristic of that species.2. The breakdown rate of ADP is related directly to the B. M. R. of that species.3. The platelet aggregation response to ADP is extremely variable even within a species, and bears little, if any, relationship to ADP breakdown.4. The breakdown of ADP added to whole blood has been studied both in normal subjects and in patients with myocardial infarctions. The breakdown patterns were found to be identical.5. The ADP-ase activity of whole blood was localised almost entirely in the white cells.